Review of Christian Mauder: In the Sultan’s Salon. Learning, Religion, and Rulership at the Mamluk Court of Qāniṣawh al-Ghawrī (r. 1501–1516). - Ståhlberg, Sabira (Studia Orientalia Electronica, 2022)
Review of Christian Mauder: In the Sultan’s Salon. Learning, Religion, and Rulership at the Mamluk Court of Qāniṣawh al-Ghawrī (r. 1501-1516). (Islamic History and Civilization. Studies and texts volume 169/1). Leiden: Brill 2021. 2 volumes. ISSN 0929-2403; ISBN 978-90-04-43576-6 (hardback, set); ISBN 978-90-04-47100-9 (hardback, vol. 1); ISBN 978-90-04-47101-6 (hardback, vol. 2); ISBN 978-90-04-44421-8 (e-book).